Couple versus Single Mother Group Treatment: A Comparative Study - Shechtman, Zippi; Danino, Maly (Advances in Social Sciences Research Journal, 2017)
This study compared couple versus single-mother treatment in group. Ninety-three participants from nine small groups received treatment in one of two conditions: mothers (47) and 23 couples (n = 46). Results showed positive pre-post outcomes on stress and parental coping for participants in both conditions, with no difference between them. However, differences were found at post-follow up (after six months), with parents treated as couples managing to retain gains following treatment, compared with mothers treated alone, who even showed some deterioration with time. Only one gender difference was found—fathers were less motivated to engage in treatment in all three time measurements. Regarding the important role fathers have in their child’s development and the positive gains when treated as a couple, fathers should be encouraged to engage more in treatment, and an interpersonal group of an expressive-supportive modality may be a viable way for fathers to do so.